STRATEGI KEPALA SEKOLAH DALAM MENCIPTAKAN BUDAYA RELIGIUS DI SEKOLAH - Asnawi Asnawi; Bambang Budi Wiyono; Asep Sunandar (Universitas Negeri Malang, 2020)
Abstrak : This study aims to find out, (1) steps the school principal creates religious culture, (2) forms of religious culture in schools, (3) ways of socializing and implementing religious culture, (4) support of teachers and school members in creating religious culture, ( 5) how to overcome the problem of creating a religious culture. This research uses a qualitative approach design, with a case study research design. The location of this research is at Public SHS 9 Malang. Data collection techniques through interviews, observation, and documentation. The analysis technique used is reduction, data display, and data verification. The results of this study (1) the step of the school principal creating a religious culture begins with a meeting consisting of a core team to design an outline of the relevant activities then in consultation with the teachers, (2) the forms of religious culture in the school are Dhuha pray, DhuhurPray and AsrPray in congregation, study of the yellow book, Friday prayers in congregation and princess activities, non-Muslim students religious guidance, training to become qotib, istighosah, ramadhanpondok activities, Commemoration of Islamic Holidays, (3) socialization and implementation of Religious culture through social media, print , electronics, school websites, and verbally. While the implementation is a strategy that has been designed from the stages of planning, implementing, and habituating in daily life in the school environment, (4) teacher and school community support in creating a religious culture including, the teacher goes to the mosque when he hears the call to prayer, starts the lesson by praying, and encourage students to pray Dhuha before the lesson begins, students lead literacy, students become qotib, educational staff every Friday-morning at the morning apple to deliver information on activities carried out on that day. Parental support is parents doing zakat fitrah and zakat mal at school, the establishment of a school mosque is an idea and contribution from parents of students; (5) The way to overcome problems in creating a religious culture is by evaluating systematically and carried out by related parties. Keywords: Strategy, headmaster, religious culture Abstrak : Penelitian ini bertujuanmengetahui, (1)langkah-langkah kepala sekolah menciptakan budaya religius, (2) bentuk budaya religius di sekolah, (3) cara sosialisasi dan implementasi budaya religius, (4) dukungan guru dan warga sekolah dalam menciptakan budaya religius, (5) cara mengatasi masalah menciptakan budaya religius. Penelitian ini menggunakan rancangan pendekatan kualitatif, dengan rancangan penelitian studi kasus. Lokasi penelitian ini di SMA Negeri 9 Malang. Teknik pengumpulan data melalui wawancara, observasi, dandokumentasi. Teknik analisis yang digunakan yaitu reduksi, display data, dan verifikasi data. Hasil dari penelitian ini (1) langkah kepala sekolah menciptakan budaya religius diawali rapat yang beranggotakan tim inti untuk merancang segara garis besar terkait kegiatan barulah di musyawarahkan dengan para guru, (2) bentuk-bentuk budaya religius yang ada di sekolah adalah Salat Dhuha, Salat Dhuhur dan Ashar berjamaah, kajian kitab kuning, Salat jumat berjamaah dan kegiatan keputrian, siswa non muslim pembinaan keagamaan, pelatihan menjadi qotib, istighosah, kegiatan pondok ramadhan, Peringatan Hari Besar Islam, (3) sosialisasi dan implementasi budaya Religius melalui media sosial, cetak, elektronik, website sekolah, dan secara lisan. Sedangkan implementasinya adalah strategi yang sudah dirancang dari tahap pereencanaan, pelaksanakan, dan pembiasaan di keseharian di lingkungan sekolah, (4) dukungan guru dan warga sekolah dalam menciptakan budaya Religius meliputi, guru menuju masjid saat mendengar adzan untuk menunaikan Salat,mengawali pelajaran dengan berdoa, dan menganjurkan siswa untuk Salat Dhuha sebelum pelajaran dimulai, siswa memimpin literasi, siswa menjadi qotib, tenaga kependidikan setiap hari selasa-jumat dilakukan apel pagi untuk penyampaian informasi kegiatan yang dilakukan pada hari itu. Dukungan orangtua adalah orangtua melakukan zakat fitrah dan zakat mal disekolah, berdirinya masjid sekolah merupakan gagasan dan sumbangan dari orangtua siswa; (5) Cara mengatasi masalah dalam menciptakan budaya Religius adalah dengan evaluasi yang dilakukan secara sistematis dan dilaksanakan oleh pihak-pihak terkait. Kata kunci : strategi, kepala sekolah, budaya religius